Pharmacological characterization of a novel potent, selective, and orally active orexin 2 receptor antagonist, SDM‐878 - Shunsuke Maehara; Natsuko Yuge; Chika Higashi; Takumi Ota; Junji Furukawa; Takashi Takeuchi (Wiley, 2020)
Abstract Aims Recently, we identified a novel orexin 2 (OX2) receptor antagonist, SDM‐878 (2‐(3‐(2‐(1H‐pyrazol‐1‐yl)nicotinoyl)‐3,8‐diazabicyclo[3.2.1]octan‐8‐yl)‐3‐methoxyisonicotinonitrile). The purpose of the present study is to characterize the in vitro and in vivo pharmacological effects of SDM‐878. Methods The in vitro potency and selectivity of SDM‐878 were examined in CHO cells that exhibit stable expression of human orexin 1 (OX1), human orexin 2 (OX2), rat OX1, and rat OX2receptors. Then, the plasma half‐life, oral bioavailability, and brain penetration of SDM‐878 were examined in rats. The in vivo effect of SDM‐878 in rats was tested using electroencephalography (EEG). The target engagement of SDM‐878 in the rat brain was examined using the antagonistic effect against hyperlocomotion caused by the intracerebroventricular administration of the OX2 receptor agonist, ADL‐OXB ([Ala11, d‐Leu15]‐orexin B). Results SDM‐878 showed potent inhibitory activities for human and rat OX2 receptors with IC values of 10.6 and 8.8 nM, respectively, and approximately 1000‐fold selectivity against the OX1receptor. In rat studies, SDM‐878 exhibited a relatively short half‐life in plasma, oral bioavailability, and good brain penetration. These data indicate that SDM‐878 is a potent, selective, orally active, and brain‐penetrable OX2receptor antagonist. In behavioral studies using rats, SDM‐878 (100 mg/kg) antagonized hyperlocomotion caused by intracerebroventricular administration of ADL‐OXB. SDM‐878 exhibited a potent sleep‐promoting effect at the same dose (100 mg/kg) in a rat EEG study. Conclusion Our results suggest that SDM‐878 is likely to be a good pharmacological tool for investigating the role of the OX2receptor and may have therapeutic potential for the treatment of insomnia.